2014
DOI: 10.1073/pnas.1321507111
|View full text |Cite
|
Sign up to set email alerts
|

Tetherin antagonism by Vpu protects HIV-infected cells from antibody-dependent cell-mediated cytotoxicity

Abstract: Significance HIV-1 viral protein U (Vpu) facilitates virus release from infected cells by down-regulating and degrading tetherin, a transmembrane protein upregulated by IFN that impedes the detachment of enveloped viruses from infected cells. Here we show that this activity of Vpu protects HIV-infected cells from antibodies that are capable of directing their elimination by antibody-dependent cell-mediated cytotoxicity. A direct implication of these observations is that tetherin serves as a link betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
164
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(175 citation statements)
references
References 53 publications
10
164
1
Order By: Relevance
“…The HIV-1 accessory proteins Nef and Vpu help protect HIV-1-infected cells from ADCC by decreasing the overall amount of Env at the cell surface (11)(12)(13)(14), and by down-regulating CD4 (11,12), which otherwise engages Env, induces the CD4-bound conformation and exposes CD4i epitopes. These epitopes are readily recognized by several well-established ADCC-mediating Abs isolated from chronically infected individuals or RV144 vaccinees (12) or by sera from HIV-1-infected individuals, which are known to have a large fraction of nonneutralizing CD4i Abs (11,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HIV-1 accessory proteins Nef and Vpu help protect HIV-1-infected cells from ADCC by decreasing the overall amount of Env at the cell surface (11)(12)(13)(14), and by down-regulating CD4 (11,12), which otherwise engages Env, induces the CD4-bound conformation and exposes CD4i epitopes. These epitopes are readily recognized by several well-established ADCC-mediating Abs isolated from chronically infected individuals or RV144 vaccinees (12) or by sera from HIV-1-infected individuals, which are known to have a large fraction of nonneutralizing CD4i Abs (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in CD4 degradation, Vpu also antagonizes a restriction factor, Tetherin/bone marrow stromal antigen 2 (BST-2), which normally inhibits retroviral release (31,32). Viruses lacking Vpu remain trapped at the cell surface, resulting in an accumulation of exposed Env (11)(12)(13)(14). Therefore, Nef and Vpu can indirectly modulate Env-CD4 interaction at the surface of infected cells through CD4 and BST-2 down-regulation (11,12).…”
Section: Env-cd4 Interaction Enhances Recognition Of Hiv-1-infected Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Vpu potently counteracts BST‐2‐mediated ADCC activity 54, 55 via a mechanism that is not clearly understood (Fig. 2 #4).…”
Section: Viral Antagonists Of Bst‐2 and Neutralization Of Bst‐2 Antivmentioning
confidence: 99%
“…It has been shown that HIV-1 minimizes the exposure of this ADCC-susceptible Env conformation using a highly sophisticated strategy to keep Env on the surface of infected cells in the unbound "closed" conformation. HIV-1 accomplishes this through its accessory proteins Nef and Vpu, which decrease the overall amounts of Env (via Vpu-mediated BST-2 downregulation) and CD4 at the cell surface (13)(14)(15)(16). In addition, decreased amounts of Env at the cell surface due to efficient internalization also help the virus to avoid ADCC responses (17).…”
mentioning
confidence: 99%